†Ellimma longipectoralis sp. nov. (Teleostei: Clupeomorpha: †Ellimmichthyiformes) from the Aptian of the Santos Basin, southeastern Brazil. (March 2020) - Polck, Márcia Aparecida dos Reis; Gallo, Valéria; de Figueiredo, Francisco J.; Viana, Samuel Magalhães; dos Santos, Viviane Sampaio Santiago; de Queiroz Neto, João Villar; Jahnert, Ricardo Jorge
Abstract: We described herein † Ellimma longipectoralis sp. nov., a new paraclupeid fish from the Aptian laminites of the pre-salt section in the Barra Velha Formation, Santos Basin, southeastern Brazil. This new species is represented by a single articulated specimen with elongate body and expanded pectoral region. It differs from the other nominal species of † Ellimma († E. branneri and † E. cruzae ) mainly by having a long pectoral fin (with 10–11 fin rays, reaching the seventh pleural rib), a complex arrangement of the supraorbital sensory canal in the frontal, predorsal scutes ornamented with straight ridges, and edentulous jaws and palate. This is a new occurrence of †ellimmichthyiforms in the Early Cretaceous and in offshore sedimentary basin, extending their geographical distribution southwards in the Western Gondwana. Highlights: A new paraclupeid fish is described from the Aptian of the pre-salt section on the Southeastern Brazil. The new species has an elongate body and expanded pectoral region. This is a new occurrence of †ellimmichthyiforms in the Early Cretaceous and in offshore sedimentary basin. This new occurrence extends the geographical distribution of †ellimmichthyiforms southwards in the Western Gondwana.